Effects of Loom Speed, Insertion Air Pressure, and Yarn Type on Fabric Air Permeability: Case Study on Air Jet Loom - Anmen Admas; Alemayehu Assefa (Journal of Engineering)
The air permeability of the fabric is affected by the type of yarn used, the loom speed, and the amount of air pressure delivered by the relay nozzles. In this study, 21 Ne of ring and rotor spun yarns were used as a weft in an air jet loom. Loom speed and left- and right-side relay nozzles pressure in a range of 400–600 RPM, 2–4 bar, and 3–6.5 bar, respectively, were taken as additional factors. To develop and analyze the experiment, a full factorial design was used. It was observed that the air permeability of rotor spun weft yarn fabric’s is greater than ring spun weft yarn fabrics. Furthermore, when the speed of the loom increased and the left- and right-side relay nozzles air pressure decreased, the fabric’s air permeability increased and vice versa.